2018
DOI: 10.24850/j-tyca-2018-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de las sequías mediante la comparación de tres índices multiescalares en Zacatecas, México

Abstract: La sequía es uno de los desastres naturales más frecuentes en el centro-norte de México, y su identificación y caracterización son cruciales para tratar de mitigar sus efectos. Se analizó la evolución de las sequías meteorológicas en

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In general, the studied area is characterized by frequent and, in some cases, severe drought intensity in the central and northern parts of the state, where the main agricultural areas are located. These results are in general agreement with those obtained by other studies analyzing drought in the state of Zacatecas using different meteorological drought indices, among them the Standardized Precipitation Index (SPI) [42,58,96], the Reconnaissance Drought Index (RDI) [42,58], and the Standardized Precipitation-Evapotranspiration Index (SPEI) [42]. These studies found that the most severe droughts occurred during the study period between 2005 and 2011 [58,96], and they also identified the most important dry periods, such as 1995-1997, 1999-2001, and 2011-2012 [41,42].…”
Section: Areas Affected By Agricultural Droughtsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, the studied area is characterized by frequent and, in some cases, severe drought intensity in the central and northern parts of the state, where the main agricultural areas are located. These results are in general agreement with those obtained by other studies analyzing drought in the state of Zacatecas using different meteorological drought indices, among them the Standardized Precipitation Index (SPI) [42,58,96], the Reconnaissance Drought Index (RDI) [42,58], and the Standardized Precipitation-Evapotranspiration Index (SPEI) [42]. These studies found that the most severe droughts occurred during the study period between 2005 and 2011 [58,96], and they also identified the most important dry periods, such as 1995-1997, 1999-2001, and 2011-2012 [41,42].…”
Section: Areas Affected By Agricultural Droughtsupporting
confidence: 91%
“…In the case of Mexico, there are very few comprehensive assessments of drought risk using spatially and temporally consistent information on the possible hazard complemented by exposure factors and drought vulnerability [37]. The vast majority of research on drought carried out in the country has focused on evaluating the meteorological drought hazard based on rainfall records obtained from weather stations (i.e., [38][39][40][41][42]). However, weather stations are not evenly distributed in the country, and fewer and fewer stations remain operational due to a lack of maintenance budget and personnel, which is why historical climatological records are not spatially or temporally consistent and they must be subjected to quality control, homogenization, and data filling processes [43,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant climate in most of Zacatecas is dry and semi-dry (73%); 17% of the territory, in the east of the state, is temperate subhumid; in 6% of the territory, mainly the north and northeast regions, the climate is very dry, and the remaining 4% of the state, in the south and southwest, (e) soil use and vegetation. Source: prepared by the authors using data from [43][44][45][46].…”
Section: Description Of Study Areamentioning
confidence: 99%
“…The dry and semi-dry climate of the state is a limitation for agriculture, which is irrigated and seasonal and is one of the main economic activities in the state. [41].…”
Section: Description Of Study Areamentioning
confidence: 99%